Pengaruh Jumlah Penduduk, Pengangguran dan Pendidikan terhadap Tingkat Kemiskinan di Wilayah Indonesia Bagian Timur Tahun 2019-2023 - Leony Angelica Weru; Novi Theresia Kiak; Olivia L.E Tomasowa (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This study aims to analyze the effect of population, unemployment rate, and education level on poverty levels in eastern Indonesia in 2019–2023. This study is a quantitative study with a descriptive approach using secondary data obtained from official publications of the Central Statistics Agency and other reliable sources. The analysis method used is the panel data regression analysis technique. The results of the study indicate that partially the variables of population, unemployment rate, and education level have a significant effect on poverty levels. Simultaneously, these three variables also have a significant effect on poverty levels in eastern Indonesia. These findings indicate that increasing education and decreasing unemployment rates can be effective strategies in reducing poverty. This study is expected to be a reference for local governments in formulating more targeted and sustainable socio-economic development policies.